Citrus Peel Waste as an Electrolyte Solution for Energy Storage in Bio-Batteries - I Wayan Suriana; Ida Ayu Dwi Giriantari; Wayan Gede Ariastina; I Nyoman Setiawan (PT Mattawang Mediatama Solution, 2025)
This study explores the potential of citrus peel waste as an electrolyte solution for energy storage in bio-batteries. This research offers an environmentally friendly solution to obtain clean and sustainable energy by utilizing abundant organic waste as raw material. An experimental method was conducted to analyze the ability of electrolyte solutions from citrus fruit peel waste to support bio-battery performance. The results showed that citrus peel waste has significant potential as an electrolyte solution with competitive capabilities in energy storage. The implications of this research include the development of more sustainable alternative energy technologies and the effective use of unused resources, which could be an essential step in achieving global sustainability goals.